Biomechanical investigation of impact induced rib fractures of a porcine infant surrogate model. (September 2016) - Blackburne, William B.; Waddell, J. Neil; Swain, Michael V.; Alves de Sousa, Ricardo J.; Kieser, Jules A.
Abstract: This study investigated the structural, biomechanical and fractographic features of rib fractures in a piglet model, to test the hypothesis that fist impact, apart from thoracic squeezing, may result in lateral costal fractures as observed in abused infants. A mechanical fist with an accelerometer was constructed and fixed to a custom jig. Twenty stillborn piglets in the supine position were impacted on the thoracic cage. The resultant force versus time curves from the accelerometer data showed a number of steps indicative of rib fracture. The correlation between impact force and number of fractures was statistically significant (Pearson׳s r =0.528). Of the fractures visualized, 15 completely pierced the parietal pleura of the thoracic wall, and 5 had butterfly fracture patterning. Scanning electron microscopy showed complete bone fractures, at the zone of impact, were normal to the axis of the ribs. Incomplete vertical fractures, with bifurcation, occurred on the periphery of the contact zone. This work suggests the mechanism of rib failure during a fist impact is typical of the transverse fracture pattern in the anterolateral region associated with cases of non-accidental rib injury. The impact events investigated have a velocity of 2–3 m/s, approximately 2×10 4 times faster than previous quasi-static axial and bending tests. While squeezing the infantile may induce buckle fractures in the anterior as well as posterior region of the highly flexible bones, a fist punch impact event may result in anterolateral transverse fractures. Hence, these findings suggest that the presence of anterolateral rib fractures may result from impact rather than manual compression. Graphical abstract: Highlights: We present observations and analysis of the fracture of ribs associated with an impact injury event. A piglet surrogate model has here been used to simulate infant rib fracture. The observations presented clearly simulate clinical evidence. It adds to evidence examining mechanisms of rib fracture and separates squeezing from impact events. Results suggest impact strain rate has an influence on rib deformation/fracture behavior.